Composite material, device and method for efficiently extracting uranium from salt lake water flow
By designing composite materials to convert mechanical energy from salt lake water flow into electrochemical energy, the existing uranium extraction technology has solved the problems of high energy consumption and dependence on external energy, and achieved efficient, environmentally friendly and economical uranium extraction effects.
Patent Information
- Application Number
- CN202510013557.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-06
- Publication Date
- 2025-03-21
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing uranium extraction technology has problems with high energy consumption, poor material durability, high operating complexity and dependence on external energy, especially when extracting uranium in salt lake water flow, it is difficult to efficiently utilize natural resources.
A composite material is designed, including an upper electrode layer, a bionic patterned dielectric layer and a lower electrode layer. The mechanical energy of the salt lake water flow is converted into electrochemical energy through the solid-liquid interface contact separation process to achieve efficient extraction of uranium ions.
This method greatly reduces energy consumption, improves uranium extraction efficiency, and does not require external power or light sources, and has good environmental friendliness and economic benefits.
Smart Images

Figure CN119660874A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of uranium extraction, and in particular to a composite material, a device and a method for efficiently extracting uranium from a salt lake water flow. Background Art
[0002] As an efficient and clean energy source, nuclear energy has become an important source of electricity for many countries around the world. Uranium is a key element of nuclear fuel. However, terrestrial uranium resources are limited and unevenly distributed. Traditional uranium mining not only consumes resources, but also has potential negative impacts on the environment. Therefore, finding more sustainable uranium extraction methods, especially extracting uranium from other natural resources, has become an important research direction.
[0003] There are many types of water bodies containing uranium, including salt lake water, seawater and uranium mine water. Among them, salt lakes, as natural resources rich in minerals, contain rich uranium resources, especially those salt lakes with strong evaporation, where the uranium concentration is relatively high. Extracting uranium from salt lakes can not only greatly reduce dependence on terrestrial uranium resources, but also achieve sustainable uranium resource supply through reasonable development. Extracting uranium from salt lakes has important strategic significance worldwide.
[0004] Traditional solvent extraction, adsorption and chemical precipitation are the more commonly used methods for uranium extraction. Among them, solvent extraction has a higher uranium extraction efficiency, but it requires a large amount of organic solvents and has a long process flow. Chemical precipitation separates uranium ions from wastewater in the form of precipitation by adding precipitants to wastewater, which will have a negative impact on the environment. As for the adsorption method, it is considered to be the method with the most industrial potential and is also the most widely studied uranium extraction technology for low-concentration uranium water. However, different adsorbents have different adsorption effects on uranium. The active adsorption sites decrease with the enrichment of uranium, and the adsorbed uranium will produce a strong Coulomb repulsion on the uranium ions in the solution. Once the active adsorption sites are saturated, the adsorption effect will fail.
[0005] In recent years, some emerging methods of uranium extraction, such as electrocatalysis or photocatalysis, have also been developing. Electrocatalysis and photocatalysis each have their own advantages and disadvantages in uranium extraction. The electrocatalytic method is efficient, scalable, and can accurately reduce uranium ions, but it requires a lot of electrochemical energy, has complex infrastructure, and has high maintenance requirements and costs. Photocatalysis uses solar energy, the process is environmentally friendly, and innovative materials such as titanium dioxide and metal-organic frameworks improve the extraction efficiency. However, photocatalysis relies on light, its efficiency is affected by light intensity, and the reaction rate is low. The catalyst is easily degraded and needs to be replaced regularly. In general, electrocatalysis is suitable for large-scale and efficient uranium extraction, but it has high energy and cost; photocatalysis is environmentally friendly and energy sustainable, but its efficiency drops sharply when there is insufficient light.
[0006] It is worth noting that in a salt lake environment, brine can flow naturally or artificially from higher terrain to lower terrain to form a stream, and the flow of water can provide energy for the uranium extraction process. Therefore, how to design reasonable materials and devices to utilize the flow of salt lake brine to effectively convert mechanical energy into electrochemical energy to drive uranium extraction and reduce dependence on external energy is an urgent problem to be solved. Summary of the invention
[0007] The technology of the present invention aims to solve the problems of high energy consumption, poor material durability, high operation complexity and dependence on external energy in current uranium extraction technology, and to provide a composite material, device and method for efficiently extracting uranium from salt lake water.
[0008] In order to achieve the above technical objectives, the technical solution provided by the present invention is:
[0009] A composite material for efficiently extracting uranium from salt lake water flow, the material comprising, from top to bottom, an upper electrode layer, a bionic patterned dielectric layer, and a lower electrode layer.
[0010] Specifically, the upper electrode layer can be made of common conductive metals such as aluminum, copper and other metal wires or metal strips, or a specific mask can be selected by brushing or in-situ vapor deposition to prepare conductive materials such as graphene; preferably, the length of the upper electrode material and the dielectric layer material are consistent, and the width of the upper electrode material is in the range of 5-100 microns; considering that the use environment of the upper electrode may have high humidity, acid-base corrosion, etc., it can be further grafted with a monolayer of fluorosilane or the like according to actual needs to resist the corrosion of water molecules and acid-base ions on the surface. The preferred fluorosilane monolayer can include perfluorodecyltrichlorosilane, perfluorooctyltrichlorosilane, perfluoroethyltrimethoxysilane, polysiloxane, etc. The grafting concentration is 4m 3 In the chamber, 100-1000 microliters of fluorosilane solution is chemically vapor deposited, the grafting time is controlled to be 1-6 hours, and the temperature is set to 30-90 degrees Celsius.
[0011] Specifically, the bionic patterned dielectric layer has strong mechanical stability and high-density charge storage.
[0012] Among them, the optional dielectric layer materials include polytetrafluoroethylene (PTFE), polyacrylonitrile (PAN), polycarbonate (PC), polydimethylsiloxane (PDMS), and fluorinated ethylene propylene copolymer (FEP). Most of these materials are hydrophobic and can store a large amount of static charge, exhibiting capacitor-like properties.
[0013] Specifically, the lower electrode layer can select current collector carbon felt or metal to facilitate the subsequent collection and separation of uranium metal as the lower electrode layer matrix. Due to the poor hydrophilicity of carbon felt or metal and the lack of the function of specific selective adsorption of uranyl ions, further hydrophilization treatment is required. Specific selectivity requires modifying the surface of the lower electrode layer matrix with surface groups that are selective for uranyl, such as chitosan, polyacrylamide oxime, etc.
[0014] Specifically, the sizes of the three layers of materials can be customized according to the actual working environment conditions. The width of the upper electrode needs to precisely match the width of the dielectric layer, while the remaining dimensional parameters can be carefully considered and customized according to the specific needs of the device and the inclination angle of the water flow. The materials are all reusable and have good economic benefits and environmental friendliness.
[0015] The present invention also provides a method for preparing a composite material for efficiently extracting uranium from salt lake water, comprising the following steps:
[0016] Step 1: Select a conductive material as the upper electrode layer;
[0017] Step 2: preparing a biomimetic patterned dielectric layer;
[0018] Step 3: preparing the lower electrode layer;
[0019] Step 4: Connect the upper electrode layer, the bionic patterned dielectric layer, and the lower electrode layer in sequence from top to bottom.
[0020] Furthermore, in step 2, the method for preparing the bionic patterned dielectric layer includes any one of nanoimprinting, spraying, and plasma etching, and different preparation processes are selected according to the selected material properties.
[0021] Furthermore, the nanoimprint method uses a heat preservation bag with an array protrusion structure to press on a hydrophobic film to imprint the structure, the temperature is controlled at 150-200° C., and the pressure is set to 2-10 MPa.
[0022] Furthermore, the spraying method uses an organic solvent to dissolve the hydrophobic film and then uses a high-pressure spray gun to spray in situ, the organic solvent includes one or more of n-hexane, toluene, and FC200, and the spraying pressure is controlled to be 30-60 bar.
[0023] Furthermore, the plasma etching method uses an etching gas in combination with an auxiliary etching gas to perform in-situ microstructure etching; wherein the etching gas includes one or more of SF6 and CF4; the auxiliary etching gas includes one or more of oxygen and argon; the volume ratio of the etching gas and the auxiliary etching gas is 3:1-5:1, the etching power is set to 100-300W, and the etching time is 10-60min.
[0024] Furthermore, in step 3, the preparation method of the lower electrode layer includes modifying the lower electrode layer substrate for specific selective adsorption of uranyl ions, and the specific selective modification method is to modify the surface of the lower electrode layer substrate with surface groups that are selective for uranyl, and the coating material modified with the surface groups includes any one of chitosan and polyacrylonitrile.
[0025] The specific steps of the modification method are as follows:
[0026] Step 3.1: Prepare a coating material modification solution with a concentration of 2%-5%, modify the surface of the lower electrode layer substrate by spin coating, scraping or immersion, and place it in a 60-90°C oven for drying for 6-12 hours; the solvent selected for the coating material modification solution includes one or more of methanol, acetone, ethanol, and acetic acid; the coating material modification solution is chitosan or polyacrylonitrile solution; the lower electrode layer substrate includes any one of carbon felt or metal;
[0027] Step 3.2: After the drying treatment in step 3.1, perform amide oxime treatment. The specific method of amide oxime treatment is as follows: put it in a water bath at a temperature of 50-80°C, quickly add 80-150mg / ml hydroxylamine hydrochloric acid and 60-200mg / ml sodium carbonate into the water bath, and react for 90-120 minutes. After the reaction, wash, dry and air-dry.
[0028] Furthermore, in step 4, the upper electrode layer can be fixed on the dielectric layer by gluing or casting.
[0029] The present invention also provides a device for efficiently extracting uranium from salt lake water. The device has a step-like structure, each step is provided with a water tank, the water tank is provided with the composite material according to claim 1, a drainage sheet is suspended on the electrode layer of the composite material, and the drainage sheet is connected to the water tank.
[0030] Specifically, the water trough is designed to construct the necessary loop structure between the electrodes. The purpose of connecting the drainage plate to the water trough is to direct the water flow to the upper electrode layer. The process of water falling on the upper electrode layer generates mechanical energy. The water flow converts the mechanical energy into electrochemical energy in the solid-liquid interface contact and separation process on the surface of the composite material, thereby reducing and depositing the uranium ions and enriching them in the lower electrode layer.
[0031] The present invention also provides a method for efficiently extracting uranium from salt lake water flow, which utilizes the gravitational potential energy of the height difference of salt lake water to form flow, converts mechanical energy into electrochemical energy during the solid-liquid interface contact and separation process of the water flow on the surface of the composite material, and reduces and deposits uranium ions to enrich them in the lower electrode layer.
[0032] The present invention has the following beneficial effects:
[0033] 1. Reduced energy consumption: By utilizing the water flow formed by the gravitational potential energy of the high and low drop of salt lake water, the uranium extraction process does not require external electricity or light source, which greatly reduces energy consumption and demonstrates efficient energy utilization.
[0034] 2. High uranium extraction efficiency: The high output voltage of the upper electrode layer, bionic patterned dielectric layer and specific adsorption modified carbon felt significantly improves the uranium extraction efficiency. In the experiment, for high-concentration 1000mg / l uranium-containing wastewater, the corresponding uranium extraction capacity can reach more than 900mg / g.
[0035] 3. Environmental friendliness: The entire uranium extraction process does not require additional chemical reagents or energy, avoids secondary pollution, and is environmentally friendly.
[0036] 4. Significant economic benefits: By reducing energy consumption and improving uranium extraction efficiency, the present invention significantly reduces the cost of nuclear wastewater treatment. The cost of extracting 1g of uranium is only about 1 / 10 of the cost of commercial uranium extraction. BRIEF DESCRIPTION OF THE DRAWINGS
[0037] Figure 1 This is a schematic diagram of a device for extracting uranium using salt lake water flow;
[0038] Figure 2 This is a microscopic morphology picture of the biomimetic patterned dielectric layer;
[0039] Figure 3 This is the X-ray photoelectron spectrum of carbon felt modified with chitosan;
[0040] Figure 4 This is the microscopic morphology of carbon felt after uranium extraction;
[0041] Figure 5 X-ray photoelectron spectrum of carbon felt after uranium extraction;
[0042] Figure 6 To collect X-ray diffraction patterns of uranium;
[0043] Figure 7 To collect the U4f fine spectrum of uranium's X-ray photoelectron spectrum.
[0044] Figure 1 Winning bid number:
[0045] 1-sink, 2-drainage sheet DETAILED DESCRIPTION
[0046] The technical solution of the present invention is described clearly and completely below in conjunction with the accompanying drawings. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0047] In addition, the technical features involved in the different embodiments of the present invention described below can be combined with each other as long as they do not conflict with each other.
[0048] Example 1
[0049] like Figure 1 As shown, a device for efficiently extracting uranium from salt lake water flow is shown. The device has a step-like structure, and a water tank 1 is arranged on each step. A composite material is arranged on the water tank 1. A drainage sheet 2 is suspended on the electrode layer on the composite material, and the drainage sheet 2 is connected to the water tank 1.
[0050] Specifically, the water trough is designed to construct the necessary loop structure between the electrodes. The purpose of connecting the drainage plate to the water trough is to direct the water flow to the upper electrode layer. The process of water falling on the upper electrode layer generates mechanical energy. The water flow converts the mechanical energy into electrochemical energy in the solid-liquid interface contact and separation process on the surface of the composite material, thereby reducing and depositing the uranium ions and enriching them in the lower electrode layer.
[0051] The above device is used to efficiently extract uranium from salt lake water flow, which utilizes the gravitational potential energy of the height difference of salt lake water to form flow. The water flow converts mechanical energy into electrochemical energy during the solid-liquid interface contact and separation process on the surface of the composite material, and reduces and deposits uranium ions to enrich them in the lower electrode layer.
[0052] Example 2
[0053] A method for preparing a composite material for efficiently extracting uranium from salt lake water comprises the following steps:
[0054] Step 1: Select a conductive material as the upper electrode layer.
[0055] Specifically, the upper electrode is fixed to the dielectric layer by pasting or casting a common conductive metal such as aluminum, copper or other metal wire or metal strip. It is also possible to select a specific mask by brushing or in-situ vapor deposition to prepare conductive materials such as graphene. The preferred upper electrode material and the dielectric layer material have the same length and a width in the range of 5-100 microns. Considering that the use environment of the upper electrode may have high humidity, acid-base corrosion, etc., it is also possible to further graft a monolayer of fluorosilane or the like according to actual needs to resist the erosion of the surface by water molecules and acid-base ions. The preferred fluorosilane monolayer may include perfluorodecyltrichlorosilane, perfluorooctyltrichlorosilane, perfluoroethyltrimethoxysilane, polysiloxane, etc. The grafting concentration is 4m 3 In the chamber, 100-1000 microliters of fluorosilane solution is chemically vapor deposited, the grafting time is controlled to be 1-6 hours, and the temperature is set to 30-90 degrees Celsius.
[0056] Step 2: Prepare a biomimetic patterned dielectric layer.
[0057] Specifically, a plasma etching method is adopted, fluorinated ethylene propylene copolymer (FEP) is selected as the material, and etching gases such as SF6 or CF4 are selected in combination with auxiliary etching gases such as oxygen and argon to perform in-situ microstructure etching. Specifically, the volume ratio of the etching gas and the auxiliary etching gas is controlled between 3:1 and 5:1, the power is set to 100-300W, and the etching time is selected to be 10-60min.
[0058] Step 3: Prepare the lower electrode layer.
[0059] Specifically, the material is carbon felt, which is coated with chitosan. A chitosan solution with a concentration of 2%-5% is prepared using an acetic acid aqueous solution. The carbon felt or metal is surface modified by spin coating, scraping or soaking, and placed in a 60-90°C oven for drying for 6-12 hours. After drying, an amide oxime treatment is performed. Specifically, the coated electrode is then placed in a water bath stable at 50-80°C, 80-150 mg / ml hydroxylamine hydrochloric acid and 60-200 mg / ml sodium carbonate are quickly added to the water bath, and reacted for 90-120 minutes. After the reaction, the enriched uranium electrode is washed with deionized water and air-dried in a drying oven.
[0060] Step 4: Connect the upper electrode layer, the bionic patterned dielectric layer, and the lower electrode layer in sequence from top to bottom.
[0061] Example 3
[0062] A method for preparing a composite material for efficiently extracting uranium from salt lake water comprises the following steps:
[0063] Step 1: Select a conductive material as the upper electrode layer.
[0064] Specifically, the upper electrode is fixed to the dielectric layer by pasting or casting a common conductive metal such as aluminum, copper or other metal wire or metal strip. It is also possible to select a specific mask by brushing or in-situ vapor deposition to prepare conductive materials such as graphene. The preferred upper electrode material and the dielectric layer material have the same length and a width in the range of 5-100 microns. Considering that the use environment of the upper electrode may have high humidity, acid-base corrosion, etc., it is also possible to further graft a monolayer of fluorosilane or the like according to actual needs to resist the erosion of the surface by water molecules and acid-base ions. The preferred fluorosilane monolayer may include perfluorodecyltrichlorosilane, perfluorooctyltrichlorosilane, perfluoroethyltrimethoxysilane, polysiloxane, etc. The grafting concentration is 4m 3 In the chamber, 100-1000 microliters of fluorosilane solution is chemically vapor deposited, the grafting time is controlled to be 1-6 hours, and the temperature is set to 30-90 degrees Celsius.
[0065] Step 2: Prepare a biomimetic patterned dielectric layer.
[0066] Specifically, in the nanoimprint method, polydimethylsiloxane (PDMS) is selected as the material, and an array protrusion structure insulation bag is selected to be pressed on the hydrophobic film to perform the imprinting structure. Specifically, the temperature is controlled at 150-200° C., and the pressure is set to 2-10Mpa.
[0067] Step 3: Prepare the lower electrode layer.
[0068] Specifically, the material is selected as metal, and polyacrylonitrile is coated. A polyacrylonitrile solution with a concentration of 2%-5% is prepared using an ethanol aqueous solution, and the carbon felt or metal is surface modified by spin coating, scraping or soaking, and placed in a 60-90°C oven for drying for 6-12 hours. After drying, an amide oxime treatment is performed. Specifically, the coated electrode is then placed in a water bath stable at 50-80°C, 80-150 mg / ml hydroxylamine hydrochloric acid and 60-200 mg / ml sodium carbonate are quickly added to the water bath, and reacted for 90-120 minutes. After the reaction, the enriched uranium electrode is washed with deionized water and air-dried in a drying oven.
[0069] Step 4: Connect the upper electrode layer, the bionic patterned dielectric layer, and the lower electrode layer in sequence from top to bottom.
[0070] Example 4
[0071] A method for preparing a composite material for efficiently extracting uranium from salt lake water comprises the following steps:
[0072] Step 1: Select a conductive material as the upper electrode layer.
[0073] Specifically, the upper electrode is fixed to the dielectric layer by pasting or casting a common conductive metal such as aluminum, copper or other metal wire or metal strip. It is also possible to select a specific mask by brushing or in-situ vapor deposition to prepare conductive materials such as graphene. The preferred upper electrode material and the dielectric layer material have the same length and a width in the range of 5-100 microns. Considering that the use environment of the upper electrode may have high humidity, acid-base corrosion, etc., it is also possible to further graft a monolayer of fluorosilane or the like according to actual needs to resist the erosion of the surface by water molecules and acid-base ions. The preferred fluorosilane monolayer may include perfluorodecyltrichlorosilane, perfluorooctyltrichlorosilane, perfluoroethyltrimethoxysilane, polysiloxane, etc. The grafting concentration is 4m 3 In the chamber, 100-1000 microliters of fluorosilane solution is chemically vapor deposited, the grafting time is controlled to be 1-6 hours, and the temperature is set to 30-90 degrees Celsius.
[0074] Step 2: Prepare a biomimetic patterned dielectric layer.
[0075] Specifically, the spraying method is adopted, and the material is polytetrafluoroethylene (PTFE). The hydrophobic film can be dissolved by a specific organic solvent and then sprayed in situ by a high-pressure spray gun. The preferred organic solvent is n-hexane, toluene, FC200, etc. Specifically, the spraying pressure is controlled to be 30-60 bar.
[0076] Step 3: Prepare the lower electrode layer.
[0077] Specifically, the material is selected as metal, and polyacrylonitrile is coated. A 2%-5% polyacrylonitrile solution is prepared using methanol aqueous solution, and the carbon felt or metal is surface modified by spin coating, scraping or soaking, and placed in a 60-90°C oven for drying for 6-12 hours. After drying, an amide oxime treatment is performed. Specifically, the coated electrode is then placed in a water bath stable at 50-80°C, 80-150 mg / ml hydroxylamine hydrochloric acid and 60-200 mg / ml sodium carbonate are quickly added to the water bath, and reacted for 90-120 minutes. After the reaction, the enriched uranium electrode is washed with deionized water and air-dried in a drying oven.
[0078] Step 4: Connect the upper electrode layer, the bionic patterned dielectric layer, and the lower electrode layer in sequence from top to bottom.
[0079] See also Figure 2-7 , the present invention provides a microscopic morphology of a bionic patterned dielectric layer, proving that its surface has a microscopic structure similar to the papillae of a lotus leaf. The successful grafting on the carbon felt surface was confirmed by the X-ray photoelectron spectroscopy of the carbon felt after chitosan modification. The observation results of the microscopic morphology of the carbon felt after uranium extraction and the X-ray photoelectron spectroscopy also prove that the present invention successfully extracts uranium from the uranium-containing solution, and its morphology is scaly and easy to scrape off the surface. The collected X-ray diffraction (XRD) spectrum and XPS U4f fine spectrum of uranium can be used to analyze the chemical composition and valence state of the uranium extraction material. Therefore, the rationality and effectiveness of the proposed method and device are strongly verified.
[0080] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
[0081] The above specific implementation methods are detailed descriptions of the present invention. It cannot be determined that the specific implementation methods of the present invention are limited to these descriptions. For ordinary technicians in the technical field to which the present invention belongs, several simple deductions and substitutions can be made without departing from the concept of the present invention, which should be regarded as belonging to the protection scope of the present invention.
Claims
1. A composite material for efficiently extracting uranium from salt lake water, characterized in that: The material comprises, from top to bottom, an upper electrode layer, a bionic patterned dielectric layer, and a lower electrode layer.
2. A composite material for efficiently extracting uranium from salt lake water according to claim 1, characterized in that: The bionic patterned dielectric layer material includes one or more of polytetrafluoroethylene, polyacrylonitrile, polycarbonate, polydimethylsiloxane, and fluorinated ethylene-propylene copolymer.
3. A method for preparing a composite material for efficiently extracting uranium from salt lake water, characterized in that: The steps include: Step 1: Select a conductive material as the upper electrode layer; Step 2: preparing a biomimetic patterned dielectric layer; Step 3: preparing the lower electrode layer; Step 4: Connect the upper electrode layer, the bionic patterned dielectric layer, and the lower electrode layer in sequence from top to bottom.
4. The method for preparing a composite material for efficiently extracting uranium from salt lake water according to claim 3, characterized in that: In the step 2, the method for preparing the bionic patterned dielectric layer includes any one of a nanoimprint method, a spraying method, and a plasma etching method.
5. The method for preparing a composite material for efficiently extracting uranium from salt lake water according to claim 4, characterized in that: The nanoimprinting method uses an array protrusion structure insulation bag to press on a hydrophobic film to imprint the structure, the temperature is controlled at 150-200° C., and the pressure is set to 2-10 MPa.
6. The method for preparing a composite material for efficiently extracting uranium from salt lake water according to claim 4, characterized in that: The spraying method uses an organic solvent to dissolve the hydrophobic film and then uses a high-pressure spray gun to spray in situ. The organic solvent includes one or more of n-hexane, toluene, and FC200, and the spraying pressure is controlled to be 30-60 bar.
7. The method for preparing a composite material for efficiently extracting uranium from salt lake water according to claim 4, characterized in that: The plasma etching method uses an etching gas combined with an auxiliary etching gas to perform in-situ microstructure etching; the etching gas includes one or more of SF6 and CF4; the auxiliary etching gas includes one or more of oxygen and argon; the volume ratio of the etching gas and the auxiliary etching gas is 3:1-5:1, the etching power is set to 100-300W, and the etching time is 10-60min.
8. The method for preparing a composite material for efficiently extracting uranium from salt lake water according to claim 3, characterized in that: In step 3, the preparation method of the lower electrode layer includes modifying the lower electrode layer substrate for specific selective adsorption of uranyl ions, the specific selective modification method is to modify the surface of the lower electrode layer substrate with surface groups that are selective for uranyl, and the coating material modified with the surface groups includes any one of chitosan and polyacrylonitrile.
9. A device for efficiently extracting uranium from salt lake water, characterized in that: The device has a step-like structure, each step is provided with a water tank, the composite material according to claim 1 is provided on the water tank, a drainage sheet is suspended on the electrode layer on the composite material, and the drainage sheet is connected to the water tank.
10. A method for efficiently extracting uranium from salt lake water using the device as claimed in claim 9, characterized in that: The gravitational potential energy of the height difference of salt lake water is used to form flow. The water flow converts mechanical energy into electrochemical energy during the solid-liquid interface contact and separation process on the surface of the composite material, and reduces and deposits uranium ions to enrich them in the lower electrode layer.
Citation Information
Cited By
Device, material and method for efficiently extracting uranium from salt lake water flow
CN120247182A